EFFECT OF LOOSELY BONDED INTERFACE ON PLANE WAVE PROPAGATION BETWEEN TWO HALF SPACES - Kumari, Neelam (Journal of Global Research in Mathematical Archives(JGRMA), 2016)
The reflection and transmission of plane waves from a loosely bonded interface between viscous liquid half space and a fluid saturated porous half space is presented. A longitudinal or a transverse wave impinges obliquely at the interface. Four relations among amplitudes of incidence, reflected and transmitted waves are obtained for a loosely bonded interface using suitable boundary conditions. The amplitude ratios have been computed numerically for a particular model and the results thus obtained are presented graphically. It is observed that the amplitude ratios depend not only on the angle of incidence of the incident wave, but also on material properties of the medium through which the waves traversed. Effect of bonding parameter is observed on amplitude ratios. A special case with empty porous half space medium has been obtained from the present study.Â 